HUBUNGAN POLA MAKAN ANAK, AKTIVITAS FISIK ANAK, DAN STATUS EKONOMI ORANG TUA DENGAN OBESITAS ANAK DI SEKOLAH DASAR KECAMATAN PONTIANAK SELATAN - ., Ayu Indria Paramitha (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background. Childhood obesity is serious public health problem at 21century. This is the global problem in low- and middle-income countries.The risk factors of childhood obesity are childrens dietary pattern, physicalactivity, and parents economic status. This study aims to observe theassociation between childrens dietary pattern, physical activity, andparents economic status with childhood obesity in South Pontianakelementary schools. Method. This is a cross sectional analitical study.Data obtained from the questionnaire which are distributed to mothers orcaregivers. Result. There were 120 children taken as subjects of study.Most of subjects have normal nutritional status namely 62 subjects(51,7%), 27 subjects(22,5%)were obesity, 23 subjects(19,2%)wereoverweight, 7 subjects(5,8%)were underweight and 1 subjects(0,8%)was severely underweight. The analysis data resulted that childrenssdietary pattern(p=0,000)and physical activity(p=0,007)were associatewith childhood obesity but parents economic status was not associatewith childhood obesity(p=0,475). Conclusion. There is associationbetween childrens dietary pattern and physical activity with childhoodobesity but not with parents economic status in South Pontianakelementary schools.Keywords: Childhood obesity, dietary pattern, physical activity, parentseconomic status